A fMRI study on the impact of advertising for flavored e-cigarettes on susceptible young adults. (1st May 2018) - Garrison, Kathleen A.; O'Malley, Stephanie S.; Gueorguieva, Ralitza; Krishnan-Sarin, Suchitra
Highlights: Young adult early experimenters show a product preference for sweet/fruit flavor e-cigarettes. Neural cue-reactivity was greater for sweet/fruit than tobacco flavor e-cigarette advertisements. Greater cue-reactivity to ads was associated with poorer recognition of health warnings. Exploratory eye-tracking indicated that sweet/fruit flavors on ads interfere with warning labels. Nonsmoking young adults reported greater liking and intent to try sweet/fruit flavor e-cigarettes. Abstract: Background: E-cigarettes are sold in flavors such as "skittles, " "strawberrylicious, " and "juicy fruit, " and no restrictions are in place on marketing e-cigarettes to youth. Sweets/fruits depicted in e-cigarette advertisements may increase their appeal to youth and interfere with health warnings. This study tested a brain biomarker of product preference for sweet/fruit versus tobacco flavor e-cigarettes, and whether advertising for flavors interfered with warning labels. Methods: Participants ( N = 26) were college-age young adults who had tried an e-cigarette and were susceptible to future e-cigarette use. They viewed advertisements in fMRI for sweet/fruit and tobacco flavor e-cigarettes, menthol and regular cigarettes, and control images of sweets/fruits/mints with no tobacco product. Cue-reactivity was measured in the nucleus accumbens, a brain biomarker of product preference. Advertisements randomly contained warning labels, and recognition of health warnings was tested post-scan. Visual attention was measured using eye-tracking. Results: There was a significant effect of e-cigarette condition (sweet/tobacco/control) on nucleus accumbens activity, that was not found for cigarette condition (menthol/regular/control). Nucleus accumbens activity was greater for sweet/fruit versus tobacco flavor e-cigarette advertisements and did not differ compared with control images of sweets and fruits. Greater nucleus accumbens activity was correlated with poorer memory for health warnings. Conclusions: These and exploratory eye-tracking findings suggest that advertising for sweet/fruit flavors may increase positive associations with e-cigarettes and/or override negative associations with tobacco, and interfere with health warnings, suggesting that one way to reduce the appeal of e-cigarettes to youth and educate youth about e-cigarette health risks is to regulate advertising for flavors.